"Reverse" intergovernmental transfers between regions with local public goods - John M. Hartwick (Queen's University, Department of Economics, 2009)
We report on the nature of a utility optimizing transfer from one regional government to another when local public goods are present. Computer examples reveal that small differences in regional endowments result in large differences in equilibrium outcomes for two regions, under optimal transfers. The scale effect (lower tax charge per person for the same public good in more populous regions) leads to the small region generally providing transfers to the larger region.
Keywords: H41; H77; R28; 330; intergovernmental transfers; local public goods; inter-regional resource allocation; Öffentliches Gut; Räumliche Verteilung; Regionale Disparität; Finanzausgleich; Nutzen; Theorie